Role of the Wnt/β-catenin signaling pathway in the development of HCC - Lin, Bo; Li, Mengsen (Frontiers in Immunology, 2025)
Abnormalities in the Wnt/β-catenin pathway promote the development of hepatocellular carcinoma (HCC). Mutations in CTNNB1, which encodes β-catenin, are frequently found in clinical HCC samples, as are loss-of-function mutations in signaling pathway regulators such as axis inhibition protein 1 (Axin1) and adenomatous polyposis coli (APC). The activation of the Wnt/β-catenin pathway synergizes with other oncogenic signal molecules such as c-Met or glypican-3, contributing to HCC development. Furthermore, Wnt/β-catenin pathway activation in the tumour microenvironment (TME) leads to cold tumour and resistance to immunotherapy. In this review, we discuss two models of Wnt/β-catenin signaling activation, role of Wnt/β-catenin signaling pathway in the development of HCC, the association between Wnt/β-catenin pathway and tumour angiogenesis, metastasis, and immune escape in the TME, and the targeting of this signaling pathway for HCC treatment.